2022
DOI: 10.14245/ns.2142214.107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anterior Plating on Achieving Clinically Meaningful Improvement Following Single-Level Anterior Cervical Discectomy and Fusion

Abstract: Objective:The clinical utility of anterior cervical plating for anterior cervical discectomy and fusion (ACDF) procedures remains controversial. This study aims to compare the impact of cervical plating on achievement of minimum clinically important difference (MCID) up to 2-years following ACDF.Methods: Patients undergoing primary, single-level ACDF procedures were grouped based on whether their procedure included application of an anterior cervical plate. Demographics, preoperative spinal diagnoses, operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have compared clinical outcomes and subsidence rates between ACDF with and without cervical plating. 24 Lee et al 25 found that subsidence rates were higher when cervical fusions were performed without plating. In our study, all fusions were performed with plating or with a zero-profile cage with integrated screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have compared clinical outcomes and subsidence rates between ACDF with and without cervical plating. 24 Lee et al 25 found that subsidence rates were higher when cervical fusions were performed without plating. In our study, all fusions were performed with plating or with a zero-profile cage with integrated screws.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of subsidence on lordosis may depend on variations of ACDF surgery including but not limited to cervical plating, revision following cervical disc arthroplasty, and multilevel fusion. Recent studies have compared clinical outcomes and subsidence rates between ACDF with and without cervical plating [ 24 ]. Lee et al [ 25 ] found that subsidence rates were higher when cervical fusions were performed without plating.…”
Section: Discussionmentioning
confidence: 99%
“…If non-surgical treatment is unsuccessful, anterior cervical discectomy and fusion (ACDF) is considered the best surgical treatment 3 6 . During ACDF, a conventional cage and plate (CCP) implant is often used, which prevents interbody graft dislocation and improves sagittal alignment, interbody fusion rate, and stability 1 , 5 , 7 . CCP implants, which are thinner than earlier models, do however have limitations such as the development of postoperative dysphagia, adjacent segment degeneration, and soft tissue injury 1 , 3 , 8 11 .…”
Section: Introductionmentioning
confidence: 99%